OPTIMASI ELEKTRODA PASTA KARBON (EPK) TERMODIFIKASI DALAM PENGUKURAN BUTYLATED HYDROXYTOLUENE (BHT) - Ahmad Ma'ruf (UIN AR-RANIRY, 2022)
BHT as an antioxidant is essential because it can prevent the rate of oxidative reactions from organic compounds present in the product. However, the use of BHT can have harmful effects on health because it can trigger a carcinogenic reaction. Therefore, precise and accurate instruments are needed to measure BHT concentrations. Carbon paste electrode is a renewable material that can analyze a compound currently being developed and attracts much attention. EPK has a stable response, low electrical resistance, a quickly renewable surface for electron exchange, and can be adapted for various chemical compound detection applications. EPK modified with MIP has high chemical and physical stability, an inexpensive preparation process, excellent selectivity, and sensitivity but also a fast response to the target compound. This study aims to improve the performance of MIP-modified EPK to measure BHT optimally in terms of pH, concentration, and solution components. Optimization of EPK in BHT measurement was carried out using an experimental method using voltammetry with the CV technique. The optimum composition obtained is 1:3, the optimum cycle for electropolymerization is five cycles, and the optimum pH for BHT measurement is pH 5 with a peak oxidation current of 18,937 µA. EPK-MIP optimization results obtained can be used to measure BHT with optimal performance.